Homogeneous Solution

The homogeneous solution of the 2nd order DE can be found by solving the homogeneous equation:

$\displaystyle y''(t)+2\zeta\omega_n y'(t)+\omega_n^2 y(t)=x(t)=0$ (209)

where the right hand side of the DE for the input $x(t)=0$ is zero. Substituting the assumed solution $y(t)=Ae^{st}$ and its derivatives $\dot{y}(t)=s Ae^{st},\;y''(t)=s^2 Ae^{st}$ into the DE we get

$\displaystyle (s^2+2\zeta\omega_n s+\omega_n^2)Ae^{st}=0$ (210)

As we are not interested in a trivial solution, $Ae^{st}\ne 0$, and we get an algebraic equation

$\displaystyle s^2+2\zeta\omega_n s+\omega_n^2=0$ (211)

Solving this quadratic equation we get its two roots, the two eigenvalues of ${\bf A}$:

$\displaystyle s_{1,2}=\left\{\begin{array}{ll}
\left(-\zeta\pm\sqrt{\zeta^2-1}\...
...^2}\right)\omega_n=\omega_n e^{\mp j\phi}
&\vert\zeta\vert< 1\end{array}\right.$ (212)

where

$\displaystyle \phi=\tan^{-1}\left(\frac{\sqrt{1-\zeta^2}}{\zeta}\right)$ (213)

zetaphi.png

These two roots $s_{1,2}$ are either two real numbers or a pair complex conjugate numbers, depending on whether its discriminant is greater and smaller then 0:

$\displaystyle \Delta=(2\zeta\omega_n)^2-4\omega_n^2=4\omega_n^2(\zeta^2-1)
\lef...
...y}{ll}\ge 0 & \vert\zeta\vert\ge 1\\ < 0 & \vert\zeta\vert< 1\end{array}\right.$ (214)

rootlocus2nd1.gif

For a constant $\omega_n$ and a variable $\zeta$ that changes from $-\infty$ to $\infty$, the two roots $s_1$ (red) and $s_2$ (blue) can be represented as the root locus on the complex plane.

In particular, for the RCL circuit with all $R$, $C$, and $L$ values non-negative, we have $\zeta\ge 0$, i.e., we only need to consider the root locus on the left side of the complex plain.

Given the two roots $s_1$ and $s_2$, we can write the homogeneous solution as

$\displaystyle y_h(t)=C_1 e^{s_1t}+C_2 e^{s_2t}$ (215)

where the two coefficients $C_1$ and $C_2$ can be found based on the two initial conditions $y(0)$ and $y'(0)$. If we assume $\dot{y}(0)=0$ but $y(0)=y_0$, then we get
$\displaystyle y(0)$ $\displaystyle =$ $\displaystyle y_h(t)\bigg\vert _{t=0}=C_1+C_2=y_0$  
$\displaystyle \dot{y}(0)$ $\displaystyle =$ $\displaystyle \dot{y}_h(t)\bigg\vert _{t=0}=s_1C_1+s_2C_2=0$ (216)

Solving these we get

$\displaystyle C_1=\frac{s_2}{s_2-s_1} y_0,\;\;\;\;\;\;\;\;C_2=\frac{s_1}{s_1-s_2} y_0$ (217)

and the homogeneous solution becomes:

$\displaystyle y_h(t)=y_0 \left[ \frac{s_2 e^{s_1t}}{s_2-s_1}-\frac{s_1 e^{s_2t}}{s_2-s_1} \right]
=\frac{y_0}{s_2-s_1} (s_2 e^{s_1t}-s_1 e^{s_2t})$ (218)

Alternatively, the 2nd-order LCCODE in canonical form given above can also be solved if it is coverted into a 1st-order ODE system, as shown here.

The solution takes different forms depending on the value of the damping coefficient $\zeta$.

The homogeneous responses of these four cases are plotted below. Note that in all cases, $y(0)=y_0$ and $\dot{y}(0)=0$.

SecondOrder0.png